DEVELOPMENT STAGES OF HIGH JUMPING TECHNIQUE - Tokhtaboev, Nizom (Журнал иностранных языков и лингвистики, 2022)
This article provides information about the history of the development of high jump methods (skip, wave, roll, flip and fosbury flop), analysis of records set in different ways, effective jumping methods among high jump techniques.